A Preliminary Note on Bursera delpechiana (Linaloe or Indian Lavender) - Hussain, Syed (Indian Forester, 1958)
With the spread of Spike disease on Sandal tree and failure to find a remedy for it, attention is focussed on other tree species for the extraction of Essential Oils. Bursera delpechiana the Indian Lavender tree is one of them. The present note furnishes briefiy the information regarding Climate, Soil, Phenology and Botanical description of Bursera delpechiana as also the methods of regeneration, management and utilization of the species.